SHUTER, THE INNOVATION TOOLS TO REPLACE STONE FOR HANDLINE BAIT OF TUNA - Mustasim Mustasim; Misbah Sururi; Muh Kasim; M. Ali Ulat; Muhfizar Muhfizar; Muhammad Maskur (AQUASAINS, 2022)
Tuna bait handline is used to catch small pelagic fish, the catch of which is used as tuna handline bait. Unfortunately, the tools used are natural beach stones, whose presence is dwindling, hard to find and also threatens beach abrasion. The purpose of this study was to find an effective, easy-to-use tool as a substitute for natural stone ballast in the tuna bait handline with the glass pump fishing method. The method used is the experimental method. This research is divided into two stages, namely preliminary research to determine the length of the shutter wire and the main research to determine the ideal weight and its effectiveness on the catch. Preliminary research from July to August 2021, followed by core research, namely testing shutter devices with different weights. (300gr, 400gr and 500gr) were repeated 4 times at FAD Makbon, Kab. Sorong in September 2021. Data analysis used a Completely Randomized Design, and qualitative descriptive to describe the best Shuter construction and the results of testing the effectiveness of the shutter with the fisherman's bait handline. The total fish caught on the three Shuters were 53 fish, with a total weight of 112, 66 kg. The composition of the catch consisted of 53 baby tuna (80,485 kg), 11 salmon (7,687 kg), 7 tuna (22,864 kg), and 3 skipjack tuna (1,630 kg). The length of stainless wire required for Shuter is 80 cm, the ideal Shuter weight and is stable enough to operate in FADs is 300 gr, 400 gr and 500 gr. The response of the fish caught was mostly on Shuter with a length of 80 cm and a weight of 400 gr.